Analysis of Factors Influencing the Career Development of Village Officials: A Case Study of Organizational Commitment and Culture in Kota Pari Village - Yanti, Eli Delvi; Wahyono, Teguh; Sari, Wahyu Indah; Rajali, Muhamad (Universitas Negeri Medan, 2023)
The purpose of this study was to identify and analyze the influence of commitment and organizational culture on the career development of village officials in Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency. The specific target in this research is how to improve the career development of Village Officials so that services to the community are maximized.The hypothesis in this study is to look at the influence of commitment and organizational culture on career development. MThe method that will be used in this study is a quantitative method where the quantitative method in this study is related to data that describes the state of village officials. The data analysis used was multiple linear regression analysis with statistical testing using SPSS v. 25. The results of the study show that partially and simultaneously the variables of commitment and organizational culture have a positive and significant effect on the career development of village officials in Kota Pari Village.